Koncepcja J. Rawlsa racjonalnej sprawiedliwości jako bezstronności a zagadnienia etyki życia gospodarczego - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2008)
Rawls’s theory of justice is based on Kant’s ethics and the theory of social contract. Rawls tries toobey two rules: of universalizations and universality and of the maximization for the least privileged.His theory can be used to judge the ethical position of business firms. It follows from my studies that ajust organization of a firm is rare in times of transformation. This may be another reason for massemigration and it must be taken into account in future debates of the economic development.